Classification of Natural and Thermo-Modified Peat by Class-Modeling Techniques; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Zarubin A. G. Aleksey Gennadievich (Elaboration and Simulation of Processes in Materials Science, 2016)
Title screen